Minimally invasive resection of lumbosacral pseudojoint resulting in complete resolution of a lower back pain – A case report and review of Bertolotti syndrome. (May 2018) - Yousif, Saif; Wood, Martin
Highlights: Bertolotti syndrome is pain related to an aberrant lumbosacral transitional vertebrae. Minimally invasive resection of the pseudojoint was utilised and relieved the patient of all symptoms. This is one of the first reports of minimally invasive resection and its utilization in Bertolotti syndrome. Abstract: Bertolotti syndrome describes lower back pain secondary to an anatomical lumbosacral transitional vertebrae. We present the case of a 37 year old female with chronic lower back pain with radiological evidence of an anatomical lumbosacral pseudojoint. The patient underwent minimally invasive resection of her pseudojoint with complete resolution of symptoms postoperatively. We, as the authors would like to highlight that in patients with pain secondary to an aberrant lumbosacral articulation, consideration should be given to treatment via a minimally invasive technique.